Oil in the Context of the U.S. Energy Security - Varjan, Milan (2015)
Oil is the world's most valuable energy resource without which no highly industrialized society can survive and whose availability must be guaranteed, if necessary by military. This thesis contributes to supporting this reality by analyzing the role of oil in the process of providing for the energy security in the United States. The framework introduces the concept of oil in the economy and its position in providing for the energy security.